Squamous cell carcinoma of pancreas: an unusual site of relapse from early-stage lung cancer: 12-month postsurgery. (22nd April 2013) - Sharma, Anand; Alfa-Wali, Maryam; Rodriguez-Justo, Manuel; Polychronis, Andreas
Abstract : A 57-year-old man presented with abdominal pain and backache, weight loss of 10 kg and irregular bowel movements. He was previously diagnosed with Stage IB squamous cell carcinoma of lung and had undergone lobectomy 12 months previously. Investigations including imaging revealed a cystic mass in the body and tail of the pancreas which was biopsied and it was confirmed to be a recurrence of the squamous lung cancer involving the pancreas. He was treated with systemic chemotherapy and has shown a partial response on repeat imaging. This case illustrates a rare and unusual site of relapse in lung cancer after adjuvant therapy and a key message for follow-up surveillance for these patients.